2016
DOI: 10.1093/mnras/stw1770
|View full text |Cite
|
Sign up to set email alerts
|

The RINGO2 and DIPOL optical polarization catalogue of blazars

Abstract: We present ∼2000 polarimetric and ∼3000 photometric observations of 15 γ-ray bright blazars over a period of 936 days (11/10/2008 -26/10/2012) using data from the Tuorla blazar monitoring program (KVA DIPOL) and Liverpool Telescope (LT) RINGO2 polarimeters (supplemented with data from SkyCamZ (LT) and Fermi-LAT γ-ray data). In 11 out of 15 sources we identify a total of 19 electric vector position angle (EVPA) rotations and 95 flaring episodes. We group the sources into subclasses based on their broadband spec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
52
1
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(61 citation statements)
references
References 122 publications
7
52
1
1
Order By: Relevance
“…The low synchrotron peaking objects also have higher optical polarization degree than the high-peaking objects (Angelakis et al 2016), a trend that has also been seen in the smaller sample studied in Jermak et al (2016) and earlier in the radio band (Lister et al 2011). These general trends can be explained with a simple, qualitative model where a shock moves down a jet, which has both helical and turbulent magnetic field components (see Angelakis et al 2016 for details).…”
Section: Statistical Trendsmentioning
confidence: 68%
“…The low synchrotron peaking objects also have higher optical polarization degree than the high-peaking objects (Angelakis et al 2016), a trend that has also been seen in the smaller sample studied in Jermak et al (2016) and earlier in the radio band (Lister et al 2011). These general trends can be explained with a simple, qualitative model where a shock moves down a jet, which has both helical and turbulent magnetic field components (see Angelakis et al 2016 for details).…”
Section: Statistical Trendsmentioning
confidence: 68%
“…The 2009 long term PA rotation event was monitored by different authors [9][10][11]13,18]. We could minimize the gaps between the observation and assume that the angle rotated by the smallest difference, as we shown in a schematic view in Figure 3.…”
Section: Discussionmentioning
confidence: 99%
“…On the polarimetric monitoring programs, several authors reported high variability on the polarization angle (PA) simultaneous to the 2009 high energy flares; however, the rotation sense of each episode is still under debate, which affects the interpretation of how much PA really changed during the flare events [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…The low mass of the companion to V404 Cyg, the temporal association of γ-ray excess and radio flares, and the simultaneous detection of the 511 keV annihilation line and γ-rays of higher energy all point to the jet as the origin for such emission (Loh et al 2016). Long-term monitoring of blazars indicates a correlation between γ-ray flares and optical flares; the optical emission from blazars is polarized to different degrees depending on the location of the synchrotron peak relative to the observed optical bands (Jermak et al 2016); optical and γ-ray flares, and high polarizations, are associated with the jet. Polarization measurements of the early afterglow in GRBs indicates the existence of an ordered magnetic field in a magnetized baryonic jet (Steele et al 2009;Mundell et al 2013).…”
Section: Discussionmentioning
confidence: 99%